Aplicação sustentável dos resíduos da cadeia produtiva do açaí (Euterpe Oleracea): produção de carvão ativado para adsorção dos herbicidas tóxicos ácido 2,4-diclorofenoxiacético e atrazina da água - Ramírez, Rolando José Manuel González (2024)
Adsorption with activated carbon (AC) has proven to be a promising technique in wastewater treatment due to its simplicity, efficiency, economic viability, and social acceptance. Furthermore, AC allows the use of various organic waste as raw materials. This work aimed to evaluate the removal of toxic herbicides, 2,4-dichlorophenoxyacetic acid (2,4-D) and atrazine (ATZ), in aqueous solution, using AC derived from açaí seeds (Euterpe Oleracea) produced with zinc chloride (ZnCl2). The CA was characterized using Fourier-transform infrared spectroscopy (FTIR), X-ray diffractometry (XRD), and scanning electron microscopy (SEM) techniques coupled to an energy dispersive x-ray detector (EDS), and by the Brunauer-Emmett-Teller (BET) theory for calculating surface area. The adsorption tests were carried out with variation in the initial concentration of the herbicide and variation in temperature. The CA adsorption capacity was evaluated using the isotherms and kinetics obtained from the tests; as well as by adjusting the thermodynamic parameters. The Langmuir, Freundlich, Redlich-Peterson and Sips models were applied to the isotherms; and for kinetics, pseudo-first order, pseudo-second order and Linear Driving Force (LDF) models were applied, searching for the best representation of the process. The AC formed by carbon, and with a yield of 28%, was used satisfactorily as an adsorbent in the removal of both herbicides, 2,4-D and ATZ. The removal efficiency was due to the highly porous surface (Vp = 0.467 cm3 g−1; Dp = 1.126 nm) and good surface area (SBET = 920.56 m2 g−1). In the case of 2,4-D, satisfactory results were obtained for a dosage of 0.6 g L-1 of AC, maintaining the natural pH of the solution (≈ 6.1). In the isothermal evaluation of adsorption, the increase in adsorption capacity was associated with the increase in temperature, reaching a value of 218 mg g−1 at 328 K, and the best statistical fitting was the Sips model. In the kinetic evaluation, equilibrium was reached around 120 min for concentrations ranging from 25 to 100 mg L-1 of 2,4-D, and the LDF was the best fitting model. For ATZ, good results were obtained for a dosage of 0.54 g L-1 of AC and the natural pH of the solution (≈ 6.5). When performing isothermal analysis, as in the case of 2,4-D, the increase in adsorption capacity was associated with the increase in temperature, with a maximum value of 178 mg g−1 at 328 K, with the Redlich-Peterson model being the best fit. In kinetics, different concentrations showed different equilibrium times, and the LDF was the most representative model. The thermodynamic results indicated a physical and endothermic nature in the adsorption of both herbicides. In the simulation of an industrial effluent containing pollutants such as ATZ, Diuron and 2,4-D, the AC showed a high removal of 81.45% of ATZ. Also, during an economic evaluation, it was determined that the recovery of the ATZ (desorption) from the AC and its possible sale, could generate a profit, depending on the acquisition cost of the precursor material. Therefore, these results indicate the great potential for using açaí waste to produce AC with zinc chloride, and its efficient application in the removal of 2,4-D and ATZ, adding economic and environmental value to this type of material, making his production cycle more sustainable.